2016
DOI: 10.1074/jbc.m116.722447
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Histidine-brace Copper Coordination Sphere in Auxiliary Activity Family 10 (AA10) Lytic Polysaccharide Monooxygenases

Abstract: Copper-dependent lytic polysaccharide monooxygenases (LPMOs) are enzymes that oxidatively deconstruct polysaccharides. The active site copper in LPMOs is coordinated by a histidine-brace. This utilizes the amino group and side chain of the N-terminal His residue with the side chain of a second His residue to create a T-shaped arrangement of nitrogen ligands. We report a structural, kinetic, and thermodynamic appraisal of copper binding to the histidine-brace in an auxiliary activity family 10 (AA10) LPMO from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 62 publications
7
46
0
Order By: Relevance
“…The slopes of the k obs versus [Cu 2+ ] plots yielded second‐order rate constants of 2.19 ± 0.06 × 10 6 and 1.77 ±0.04 × 10 6 M −1 ·s −1 , for Ta LPMO9A‐Ao and Ta LPMO9A‐Pp, respectively. Both linear plots cross the axes close to the origin, as previously observed in similar analysis of a family AA10 LPMO from Streptomyces lividans , Sli LPMO10E, suggesting that association rates for Cu 2+ are high compared with the dissociation rates …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The slopes of the k obs versus [Cu 2+ ] plots yielded second‐order rate constants of 2.19 ± 0.06 × 10 6 and 1.77 ±0.04 × 10 6 M −1 ·s −1 , for Ta LPMO9A‐Ao and Ta LPMO9A‐Pp, respectively. Both linear plots cross the axes close to the origin, as previously observed in similar analysis of a family AA10 LPMO from Streptomyces lividans , Sli LPMO10E, suggesting that association rates for Cu 2+ are high compared with the dissociation rates …”
Section: Resultssupporting
confidence: 79%
“…Both linear plots cross the axes close to the origin, as previously observed in similar analysis of a family AA10 LPMO from Streptomyces lividans, SliLP-MO10E, suggesting that association rates for Cu 2+ are high compared with the dissociation rates. 39 Redox potentials, assessed through equilibrium reactions with N,N,N 0 ,N 0 -tetramethyl-1,4-phenylenediamine (TMP), were determined to be 195 AE 7 mV for TaLPMO9A-Ao and 186 AE 5 mV for TaLP-MO9A-Pp.…”
Section: Cu 2+ Binding Redox Potential and Thermal Stabilitymentioning
confidence: 99%
“…The ability of LPMOs to withstand EDTA has been reported before (8) and coincides with very high reported copper affinities (8,42). Apparently, the strong binding of copper and slow off rates (43) ensure that there is no significant transfer of copper from the LPMO to EDTA, provided that the contact time is kept short, as is the case here. Accordingly, in experiments with 0.1 mM AscA as reductant and 20 M load of H 2 O 2 , EDTA had no effect on the kinetics of SmLPMO10A.…”
Section: Experimental Set-upsupporting
confidence: 88%
“…This is not uncommon for these enzymes given their high affinity for copper which is very hard to remove from glassware and buffers and is scavenged rapidly by the enzyme, making it very challenging to completely demetallate LPMOs. This should not have much influence on the measured K D as seen here, as the obtained values match closely to those published for other enzymes in this family 31,32,34 .…”
Section: +supporting
confidence: 76%
“…The breadth of the peaks also indicated that there was potentially a mixture of species present in solution, as has recently shown by Chaplin et al 34 . As previously discussed, the reduced A z  value could arise from mixing of d(z 2 ) orbital Please do not adjust margins…”
Section: Epr Spectroscopy Of Baaa10supporting
confidence: 52%